PEMENTASAN TEATER INDONESIA 2001-2005 (Analisis Rubrik Teater Majalah Tempo) - -, Nurhadi (Diksi, 2010)
This article describes titles of drama scripts or theatre performances in Indonesiareviewed in Tempo in 2001-2005. The data resources were review articles on theatres in themagazine recorded in a compact disc. The data were collected by sorting all the articles,categorizing them based on the problems, reading them carefully, and making notes onthem. The data were analyzed using the descriptive qualitative technique. The findingsshowed that theatre performances in Indonesia reviewed in Tempo in 2001-2005 included:11 foreign scripts, 7 translation scripts, 8 adaptation scripts, 29 purely Indonesian scripts,2 Javanese scripts, and 7 articles on theatres. The number of foreign, translation, andadaptation scripts was 26. This number was almost the same as that of purely Indonesianscripts (and Javanese scripts) which was 31, so that the ratio was 26:31. The findingsshowed that Tempo, in terms of its theatre orientation, reviewed domestic and foreigntheatres equally.Keywords: theatre performance, theatre column, review, Tempo magazine.